2020
DOI: 10.1155/2020/6853258
|View full text |Cite
|
Sign up to set email alerts
|

Thicknesses of Macular Inner Retinal Layers in Children with Anisometropic Amblyopia

Abstract: Objective. To investigate the thicknesses of macular inner retinal layers in children with anisometropic amblyopia using spectral domain optical coherence tomography (SD-OCT). Methods. Thirty-seven children with anisometropic amblyopia and fifty-seven children with normal vision were recruited in the study. Both eyes of children with anisometropic amblyopia and the right eyes of normal controls underwent scanning with the Spectralis OCT. The segmentation of retinal layers was performed automatically to measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In a study conducted by Park et al [ 28 ], wherein the thickness of each retinal layer was measured, significant thinning of the mGCIPL was observed in eyes with various types of visual impairment, including cases of strabismus, aniso-astigmatism, and unilateral ptosis. This finding is consistent with the results of Xia et al [ 29 ], who conducted an analysis of anisometropic amblyopia and identified a significant reduction in the thickness of two out of the three GCL quadrants and three out of the four IPL quadrants in the peripheral macular area compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Park et al [ 28 ], wherein the thickness of each retinal layer was measured, significant thinning of the mGCIPL was observed in eyes with various types of visual impairment, including cases of strabismus, aniso-astigmatism, and unilateral ptosis. This finding is consistent with the results of Xia et al [ 29 ], who conducted an analysis of anisometropic amblyopia and identified a significant reduction in the thickness of two out of the three GCL quadrants and three out of the four IPL quadrants in the peripheral macular area compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, Guagliano et al [ 30 ] detected no differences between GCC thickness in amblyopic, fellow and control eyes. However, it should be kept in mind that the GCC includes the GCL, IPL and RNFL, and studies on the thickness of the latter in visually impaired eyes also remain contradictory [ 17 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 ], making it difficult to relate the increased data to our results.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, it was shown that some of the layers examined were thicker in certain areas of the macula and thinner in others, which may suggest that different pathological changes occur in different areas of the macula. Xia et al [ 28 ] analyzed anisometropic amblyopia and found that the thickness of 2 of the 3 GCL quadrants and 3 of the 4 IPL quadrants in the peripheral macular area studied were significantly reduced compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation